Analisis Metode RGEC untuk Penilaian Kinerja pada PT Bank Mandiri (Persero) Tbk - Fitria Asmawati; Lis Setyowati (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
This research aims to analysis the soundness level of banks using the RGEC method at PT Bank Mandiri (Persero) Tbk in 2018-2021. The data studied is in the form of financial statements of PT Bank Mandiri (Persero) Tbk for 2018-2021. The data collection technique used is the documentation technique. The data analysis technique used is a qualitative descriptive analysis technique using the RGEC method. The results of this research show that Bank Mandiri for 2018-2021 is viewed from the aspect of risk profile with two ratios, namely the ratio of Non-Performing Loans for banks in a healthy condition and the ratio of Loan to Deposit Ratio for banks in a fairly healthy condition. Aspects of Good Corporate Governance get the title of very healthy. Earnings aspect with two ratios, namely the ratio of the bank's Return on Assets in a very healthy condition and the ratio of the bank's Net Interest Margin in a healthy condition. Aspects of Capital with the ratio of Capital Adequacy Ratio of the bank is in very healthy condition.